2015
DOI: 10.1155/2015/483208
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐Associated Toxicities in Obese Women with Endometrial Cancer: More Than Just BMI?

Abstract: Purpose. The study characterizes the impact of obesity on postoperative radiation-associated toxicities in women with endometrial cancer (EC). Material and Methods. A retrospective study identified 96 women with EC referred to a large urban institution's radiation oncology practice for postoperative whole pelvic radiotherapy (WPRT) and/or intracavitary vaginal brachytherapy (ICBT). Demographic and clinicopathologic data were obtained. Toxicities were graded according to RTOG Acute Radiation Morbidity Scoring C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…A study conducted by Smits et al shows that obesity and BMI over 30 kg/m 2 are not associated with higher grades of ART [ 40 ]. Similarly, another study show that obesity in young patients with endometrial cancer is not associated with the onset of genitourinary and gastrointestinal toxicities [ 41 ]. Lim et al have found that obesity reduces the rectal dose during HDR brachytherapy due to larger quantity of fat tissue in the recto-uterine space, but does not affect the occurrence of acute gastrointestinal toxicity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Smits et al shows that obesity and BMI over 30 kg/m 2 are not associated with higher grades of ART [ 40 ]. Similarly, another study show that obesity in young patients with endometrial cancer is not associated with the onset of genitourinary and gastrointestinal toxicities [ 41 ]. Lim et al have found that obesity reduces the rectal dose during HDR brachytherapy due to larger quantity of fat tissue in the recto-uterine space, but does not affect the occurrence of acute gastrointestinal toxicity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased incidence of acute gynecological radiation toxicity in young and obese patients with cancer of genital organs was noted, while urinary and gastrointestinal toxicity were not associated with obesity 58 . On the contrary, Smits et al claim that obesity and a body mass index over 30 kg/m 2 are not associated with the larger of radiation toxicity 59 .…”
Section: Genitourinary Toxicitymentioning
confidence: 95%
“…[32] In addition, overweight and obese men are more prone to developing late pelvic symptoms after radiotherapy for prostate cancer, including higher rates of rectal bleeding and nocturia [33]. Similarly, in women with endometrial cancer treated with radiation, mean BMI positively correlates with higher-grade radiation-related gynecologic and cutaneous toxicities [34]. An analysis of pulmonary tumors less than 2.5 cm from the chest wall treated with stereotactic body radiation therapy (SBRT) further found that BMI was the strongest predictor of chest wall pain after treatment, with patients whose BMI was ≥29 having nearly twice the risk of chronic chest wall pain than patients with lower BMI [35].…”
Section: Altered Metabolism Is Associated With Increased Radiation Tomentioning
confidence: 99%